2018
DOI: 10.2217/epi-2018-0132
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of miRNA–mRNA–lncRNA Networks in Severe Asthma

Abstract: Aim: This study aimed to explore the molecular mechanism of severe asthma. Materials & methods: The shared and divergent differentially expressed mRNAs (DEmRNAs), miRNAs (DEmiRNAs) and lncRNAs (DElncRNAs) in asthma and severe asthma were identified by RNA-sequencing. Severe asthma-specific and shared DEmiRNA–DEmRNA–DElncRNA interaction networks were performed. Results: Compared with normal control, 1328 DEmRNAs, 608 DElncRNAs and 63 DEmiRNAs were identified in severe asthma. Compared with asthma, 95 DEmRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 26 publications
2
29
0
Order By: Relevance
“…We exhibited that HMGB2 was increased in EC and there was a positive correlation between HMGB2 and LINC00158. Subsequently, we proved that knockdown of LINC00158 repressed EC progression through inhibiting HMGB2 LINC00158 has been speculated to participate in the development of severe asthma [20]. In our present study, we observed LINC00158 was greatly increased in EC tissues compared with the normal endometrial tissues.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…We exhibited that HMGB2 was increased in EC and there was a positive correlation between HMGB2 and LINC00158. Subsequently, we proved that knockdown of LINC00158 repressed EC progression through inhibiting HMGB2 LINC00158 has been speculated to participate in the development of severe asthma [20]. In our present study, we observed LINC00158 was greatly increased in EC tissues compared with the normal endometrial tissues.…”
Section: Discussionsupporting
confidence: 59%
“…The rst annotation of LINC00158 also known as C21orf42 has been con rmed in the sequence of human Chromosome 21 [19]. In addition, the interactions between BCL11B-LINC00158 have been speculated to participate in the development of severe asthma [20]. By using bioinformatics tools (LncBase Predicted v.2), some microRNAs are predicted as the downstream target for LINC00158.…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of large scale comprehensive analysis of lncRNA-miRNA-mRNA networks is an important step toward understanding where lncRNAs fit into the biological processes behind cancer progression. Within the last year, these analyses have been done to further our understanding of diseases including chronic obstructive pulmonary disease, abdominal aortic aneurism, asthma, and cancer (1114). By analyzing the differential expression of lncRNAs, miRNAs, and mRNAs, identification of key pathways and mechanisms of disease may become much clearer.…”
Section: Introductionmentioning
confidence: 99%
“…Glucocorticoid insensitivity is a serious and complicated problem in asthma (Adcock and Ito, 2004;Durham et al, 2011), mainly owing to the defective ligand to the glucocorticoid receptor, abnormal receptor nuclear translocation and abnormal combination with proinflammatory nuclear proteins (Adcock et al, 2008;Barnes and Adcock, 2009;Tonello and Poli, 2009). It has been discussed that lncRNAs, miRs and mRNAs were expressed differentially between the nonsevere glucocorticoid-sensitive asthma and severe glucocorticoid-insensitive asthma (Chen et al, 2019). We show a strong interest in the role of lncRNAs in the regulation of glucocorticoid sensitivity in asthma.…”
Section: Lncrnas Associated With Glucocorticoid Insensitivity In Asthmentioning
confidence: 81%